TUGAS PERUTUSAN KELUARGA KRISTEN DALAM PENDIDIKAN MORAL ANAK : Menurut Amanat Apostolik Familiaris Consortio - Moa, Antonius (UNIKA Santo Thomas, 2013)
Family is the unity of life founded with love. As the unity of person, family becomes the heart and the center of love’s actualization and “the prime place for person’s humanization. In this identity, Christian families find its essential, central, and irreplaceable rule in the mission and responsibility to become moral educator for their children. This duty is the result of dynamic and existential improvement from what is essential in the family itself. For this reason, every Christian family findsin itself the irrevocable call which determined the uniqueness of their dignity and responsibility as moral educator for their children. Now, in the reality of modern civilization, this mission becomes more important and urgent because people continually fight and struggle to live the moral values.